Mini-Craniotomy under Local Anesthesia to Treat Acute Subdural Hematoma in Deteriorating Elderly Patients - Di Rienzo, Alessandro; Iacoangeli, Maurizio; Alvaro, Lorenzo; Colasanti, Roberto; Somma, Lucia Giovanna Maria Di; Nocchi, Niccolo; Gladi, Maurizio; Scerrati, Massimo (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2017)
Background and Study Aims Surgical treatment for acute subdural hematomas (ASDHs) in elderly patients is still considered unsatisfactory. Series focusing on the use of conventional craniotomy or decompressive craniectomy in such patients report discouraging results. Glasgow Coma Scale (GCS) score at admission seems to be crucial in the decision-making process. Deteriorating patients with a GCS score between 9 and 11 are those who would benefit most from the surgical treatment. Unfortunately, elderly patients often present other comorbidities that greatly increase the risk of severe complications after major neurosurgical procedures under general anesthesia. The aim of the present study was to evaluate the feasibility of performing a mini-craniotomy under local anesthesia to treat ASDHs in a select group of elderly patients who were somnolent but still breathing autonomously at admission (GCS 9–11).Material and Methods Twenty-eight elderly patients (age > 75 years) with ASDH and a GCS score at surgery ranging from 9 to 11 were surgically treated under local anesthesia by a single burr-hole mini-craniotomy (transverse diameter 3–5 cm) and hematoma evacuation. At the end of the procedure, an endoscopic inspection of the surgical cavity was performed to look for residual clots that were not visible under direct vision.Results The median operation time was 65 minutes. Hematoma evacuation was complete in 22 cases, complete consciousness recovery was observed in all patients but one, and reoperation was required for two patients.Conclusion Historically, elderly patients with ASDH treated with a traditional craniotomy performed under general anesthesia have not had a good prognosis. Our preliminary experience with this less invasive surgical and anesthesiological approach suggests that somnolent but autonomously breathing elderly patients could benefit from this approach, achieving an adequate hematoma evacuation and bypassing the complications related to intubation and artificial respiratory assistance.
Keywords: acute subdural hematoma; brain injury; elderly; local anesthesia; minimally invasive surgery